Training on Powtoon-Based Animated Video Learning Media for English Language Teachers (MGMP): Pelatihan Media Pembelajaran Video Animasi Berbasis Powtoon Bagi Guru-Guru MGMP Bahasa Inggris - Rizkayeni Marta Marta; Ilmiyati Rahmy Jasril Jasril; Vera Irma Delianti Vera; Ermita Ermita (Institut Riset dan Publikasi Indonesia, 2023)
This training aims to enhance the quality of education by utilizing technology. The participants are English Language teachers from the MGMP in Lima Puluh Kota, Sumatra Barat, consisting of 19 participants. The training takes place at SMPN 1 Harau, Lima Puluh Kota. It employs lecture-based sessions, discussions, and demonstrations. Evaluation results indicate that the training on Powtoon-based animated video learning media significantly improves the digital literacy of the teachers.